Multifunctional nanoparticles for gene delivery and spinal cord injury - Gwak, So-Jung; Koo, Heebeom; Yun, Yeomin; Yhee, Ji Young; Lee, Hye Yeong; Yoon, Do Heum; Kim, Kwangmeyung; Ha, Yoon (WILEY, 2015)
Methylprednisolone (MP) is a glucocorticoid that is used as an anti-inflammatory agent to the treat spinal cord injury (SCI). A low molecular weight chitosan was used to synthesize chitosan-MP conjugate, which was used to evaluate the gene therapy, anti-inflammatory and anti-apoptotic effects of MP. The cytotoxicity of chitosan-MP nanoparticles and the transfection efficiency of plasmid DNA were evaluated by MTT and luciferase assays. A chitosan-MP/pDNA complexes was injected into injured spinal cord to evaluate the anti-inflammatory and anti-apoptotic effects of these complexes using terminal deoxynucleotide transferase dUTP nick end labeling (TUNEL) and ED1 staining, respectively. In addition, to evaluate the distribution of chitosan-MP/pDNA complexes, p-gal encapsulated chitosan-MP was injected into the injected site. Cell survival was similar in cells treated with chitosan-MP conjugate and untreated cells. Luciferase expression was higher in cells treated with the chitosan-MP/pDNA than cells treated with the chitosan/pDNA. The chitosan-MP/pDNA complexes also reduced apoptosis and inflammation at the injury site. These results suggest that chitosan-MP conjugation is an effective gene delivery system to treat SCI. (c) 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3474-3482, 2015.
Keywords: NUCLEAR-LOCALIZATION SIGNAL; IN-VIVO; FUNCTIONAL RECOVERY; METHYLPREDNISOLONE; CHITOSAN; TRANSFECTION; THERAPY; CELLS; CARRIERS; VECTORS